1988
DOI: 10.1063/1.342051
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible sputtering and properties of Y-Ba-Cu-O films of various thicknesses

Abstract: One goal of this work was to develop a reproducible method of preparing high quality Y-Ba-Cu-O superconducting films and to study their properties versus thickness. This was accomplished by rf diode sputtering from a single target. Twenty-seven depositions were made using a target containing 8.9-at. % Y, 37.3-at. % Ba, and 53.8-at. % Cu. Film thicknesses ranged from 0.09 to 2.4 μm. The film compositions obtained were 15.6±1.0-at. % Y, 35.8±1.0-at. % Ba, and 48.7±1.7-at. % Cu for the mean and standard deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…For thicker films, the thickness of this layer remains constant at 0.4 pm thick as shown by the horizontal line in the figure. This model is consistent with the observations of Luborsky et al, except that in their case the breakpoint thickness was 0.25 pm [2]. Since Jc is highest in the direction perpendicular to the c-axis of YBCO, we assume to first order that all the current is carried in the bottom layer of the films.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…For thicker films, the thickness of this layer remains constant at 0.4 pm thick as shown by the horizontal line in the figure. This model is consistent with the observations of Luborsky et al, except that in their case the breakpoint thickness was 0.25 pm [2]. Since Jc is highest in the direction perpendicular to the c-axis of YBCO, we assume to first order that all the current is carried in the bottom layer of the films.…”
Section: Resultssupporting
confidence: 65%
“…It can be seen that the decrease of Jc shown by the data is faster than that predicted by the model based on the microstructural observations. It is interesting that a similar model was found to be in rough agreement with data for sputtered films which contained nonepitaxial material [2].…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The YBCO coated conductors with a current density over 1 mA/cm 2 have been demonstrated [2,4,5]. However, it has been reported that the J c decreases rapidly as the thickness of an epitaxial YBCO layer increases either on a single-crystal substrate or a metallic substrate [6][7][8][9]. The reason for the J c drop, which seems to be universal regardless of the deposition technique, is not clear.…”
Section: Introductionmentioning
confidence: 92%
“…The reason for the J c decrease with thickness has been unclarified yet. In the literatures [5][6][7][8][9][10][11], however, several reasons have been suggested for J c decrease with thickness, including a transition from c-axis to a-axis orientation, a loss of in-plane and out-of-plane textures, a decrease in the number of pinning sites, and a change in the microstructure. From this viewpoint, it must be worthwhile to investigate J c dependency of film thickness for other LREBCO films.…”
Section: Introductionmentioning
confidence: 94%